Unusual Presentations of Birth Related Cervical Spinal Cord Injury - Lee, Chien-Chung; Chou, I-Jun; Chang, Yi-Jung; Chiang, Ming-Chou (Frontiers in Pediatrics, 2020)
Neonatal spinal cord injury is a rare complication of birth trauma by difficult delivery. The typical manifestations are often catastrophic, include decreased or absent movement, loss of reﬂexes, apnea or periodic breathing, and a lack of response to painful stimulation. The outcome is usually fatal or severe, with long-term sequelae of respiratory insufficiency, limb weakness, or even paralysis of the limbs. We describe a male neonate with a C2 spinal cord injury who was born smoothly by vaginal delivery and was unnoticed initially due to unusual subtle symptoms. He presented with hoarse voice, swallowing dysfunction, decreased movement of upper limbs and hypercapnia. After receiving corticosteroid therapy and rehabilitation, he recovered much except that he still needed ventilator support at night.